Pemberdayaan Perpustakaan Di Madrasah Tsanawiyah Al- Washliyah Medan Labuhan - Nabillah Mawaddah (Yayasan Salam Cerdas Al-Fattah, 2025)
This paper describes the condition of the Madrasah Tsanawiyah Al Washliyah library which is not suitable as a literacy facility. The library room is used as a temporary warehouse, the lack of facilities such as bookshelves, tables, chairs and fans, and the limited reading collection are the main obstacles in supporting literacy activities at school. This study used a qualitative method with direct observation techniques and interviews with principals, teachers and students as primary data sources and documentation as secondary data. Despite the limited conditions, the school still tries to empower the library through outdoor literacy activities and makeshift book-based learning. Collaboration between teachers and students is an important strategy in maintaining the library's function as a learning resource. This finding shows a high spirit of literacy in the midst of limited facilities. Therefore, government attention is needed to improve the quality and function of madrasah libraries. A proper library will encourage increased interest in reading and learning quality. This study recommends policy interventions in developing madrasah libraries as literacy centers for Islamic education.